Pengaruh Custumer Experience Dan Kualitas Pelayanan Terhadap Re -Visiting di Objek Wisata Ke’te Kesu Toraja - membia, tania; Pali, Elisabet Pali; Pasulu, Isak (CV. ITTC INDONESIA, 2024)
This research aims to analyze the role of customer experience and service quality in influencing the revisit rate at the Ke’te Kesu tourist attraction. Using a quantitative approach, this study examines the impact of customer experience andservice quality the desire to return to the same tourist destination. The research sample consists of 140 respondents selected through purposive sampling techniques. Data analysis is conducted using SPSS 29. The results of this study indicate that customer experience and service quality have an impact on driving the revisit rate at the Ke’te Kesu tourist attraction. The coefficient of determination in this study is 0.275 or 27.5%.